Review Jurnal Daun Sembung (Blumea balsamifera) Sebagai Tanaman Obat Modern - Putri, Jelita Annisa; Hakim, Ali Rakhman; Amanda, Era Dea; Ihyadin, Hafiz; Irpiana, Irma; Putri, Lidia Risma (Jurnal Pelayanan Kefarmasian dan Sains, 2025)
Background: The use of traditional medicinal plants in Indonesia has long been an integral part of public health culture, one of which is sembung leaf (Blumea balsamifera). This plant is widely known for its bioactive compounds such as flavonoids, essential oils, triterpenoids, and alkaloids, which contribute to its antibacterial, antioxidant, anti-inflammatory, and potential anticancer activities. Objective: This article aims to review recent research findings on the chemical constituents and biological activities of sembung leaf through a literature review approach. Method: This study employed a journal review method by collecting and analyzing scientific articles that discuss Blumea balsamifera. Results: Based on the analysis of several studies, sembung leaf has been proven to possess strong antibacterial and antioxidant activities, as well as potential as an anticancer and anti-inflammatory agent. However, although its benefits have been demonstrated in vitro, further clinical research is needed to confirm its efficacy and safety in modern medicine. This review is expected to serve as a foundation for the future development of herbal medicines based on sembung leaf. Conclusion: Blumea balsamifera is a medicinal plant with great potential in modern therapeutics. Moreover, its widespread traditional use further supports its efficacy in herbal medicine.